Comparison of the histopathological differences between the disc material and posterior longitudinal ligament in patients with lumbar disc herniation: A focus on the etiopathogenesis - Kilitci, Asuman (Ann Saudi Med, 2021)
BACKGROUND: Lumbar disc herniation (LDH) occurs owing to the inability of the posterior longitudinal ligament (PLL) to preserve the disc material within the intervertebral space. There is apparently no study that has investigated the histopathological changes occurring in both PLL and disc material in patients with LDH. OBJECTIVE: Investigate and compare the histopathological changes occurring in PLL and disc material of the patients who underwent a surgical operation for LDH. DESIGN: Descriptive, cross-sectional. SETTING: Pathology and neurosurgery departments of a tertiary health care institution PATIENTS AND METHODS: The study included patients who underwent surgical operation for LDH from January 2018 to May 2019 and whose PLL and disc material were removed together, and had disc degeneration findings that were radiologically and histologically concordant. MAIN OUTCOME MEASURES: PLL degeneration scores according to the histopathological findings, changes in disc materials according to the MRI findings, disc degeneration scores according to the histo-pathological findings. SAMPLE SIZE: 50. RESULTS: MRI and histological examinations showed fully degenerated black discs (Grade 2) in 12 patients, partially degenerated discs (Grade 1) in 29 patients and fresh/acute discs (Grade 0) in 9 patients. The PLL showed grade 0 degeneration in 2 patients, grade 1 degeneration in 23 patients, and grade 2 degeneration in 25 patients. PLL degeneration grades were higher than the disc degeneration grades (P=.002). CONCLUSION: Longitudinal ligament degeneration can play a significant role in the pathogenesis of LDH. To the best of our knowledge, this study represents the first to focus on the histopathological changes occurring in both the PLL and disc material in patients with LDH. LIMITATIONS: Small sample, retrospective CONFLICT OF INTEREST: None.